Mathematical Literacy Ability on Reciprocal Teaching Models in Term of The Independent Learning Student - Wesna, Merry; Wardono, Wardono; Masrukan, Masrukan (Educational Management, 2021)
Mathematical literacy ability and learning independence are very important for all students in learning mathematics. The purpose of this study was to analyze mathematical literacy skills in the reciprocal teaching model in terms of student learning independence. This research is qualitative. Students who are the subjects in this study are 8th-grade students of SMPN 7 Pontianak. In this study, the subjects were selected based on high learning independence, moderate learning independence, and low learning independence. The data analysis technique used in this research is data reduction, data presentation, and conclusion drawing. Based on the results of the study, it shows that students' mathematical literacy skills in terms of high learning independence can use all indicators of mathematical literacy abilities maximally, complete each given task confidently and be able to complete tasks correctly. Students with moderate learning independence can use several indicators of mathematical literacy for a relatively long time and have a little difficulty in some of the problems that have to be done. Students at low learning independence and always expect help for the completion of given tasks.